2006
DOI: 10.1016/j.immuni.2006.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Polarization of Human TH2 Central Memory T Cells by Thymic Stromal Lymphopoietin-Activated Dendritic Cells

Abstract: The identity of TH2 memory cells and the mechanism regulating their maintenance during allergic inflammation remain elusive. We report that circulated human CD4+ T cells expressing the prostaglandin D2 receptor (CRTH2) are TH2 central memory T cells, characterized by their phenotype, TH2 cytokine production, gene-expression profile, and the ability to respond to allergens. Only dendritic cells (DCs) activated by thymic stromal lymphopoietin (TSLP) can induce a robust expansion of CRTH2+CD4+ TH2 memory cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
291
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(311 citation statements)
references
References 47 publications
13
291
0
7
Order By: Relevance
“…ϩ T-cells cultured with TSLP-DCs produced significantly high amounts of Th2 cytokines, such as IL-4, and low amounts of IFN-␥, as reported previously (38). Furthermore, these cells produced more TGF-␤ and IL-10 than naïve CD4 ϩ T-cells cultured with iDCs or LPS-DCs (Fig.…”
Section: Tslp-dcs Differentiate Cd4supporting
confidence: 85%
See 1 more Smart Citation
“…ϩ T-cells cultured with TSLP-DCs produced significantly high amounts of Th2 cytokines, such as IL-4, and low amounts of IFN-␥, as reported previously (38). Furthermore, these cells produced more TGF-␤ and IL-10 than naïve CD4 ϩ T-cells cultured with iDCs or LPS-DCs (Fig.…”
Section: Tslp-dcs Differentiate Cd4supporting
confidence: 85%
“…Consistent with our results, TSLP blunted the production of IL-12p70, TNF-␣, IFN-␥, or mRNA encoding IL-12 by human dendritic cells and type 1 IFN family members that induce Th1 differentiation (29,44,45). Recent studies have shown that TSLP-DCs induced the expansion of CD4 ϩ and CD8 ϩ T-cells and the differentiation of naïve CD4 ϩ T-cells toward Th2 cells that produced IL-4, IL-13, and TNF-␣ but not IL-10 and IFN-␥ (38,45). In addition, TSLP-DCs have been reported to prime CD8 ϩ T-cells into IL-5-and IL-13-producing effector cells exhibiting poor cytotoxic activity (46).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that TSLP functions upstream of IL-13 in the skin and lung allergic inflammation [12,13]. Given the current findings, TSLP may act both upstream and downstream of IL-13 and contribute to the initiation and maintenance of allergic inflammation; TSLP acting upstream of IL-13 may play an important role in the differentiation of Th2 type cells or in the activation of mast cells to produce IL-13 [1, 2, 4, 21] whereas TSLP acting downstream of IL-13 may play an important role in the regulation of Th2 cell function [25], in the maintenance of memory Th2 cells [26], and in the production of chemokines associated with inflammation [27] (Fig. 3).…”
Section: Il-13 Induces Tslp Expression In Normal Trachea Lung and Smentioning
confidence: 99%
“…In this complex procedure, many chemokines, (such as CCL1, CCL2, CCL11, CCL13, CCL18, CCL20, CCL21, and CCL26) interact with various immune effector cells through their receptors(D.Y. Leung et al, 2004;Homey et al, 2006). AD is a disease with the participation of whole body immune system, and that the immunologic abnormality is not limited to the skin.…”
Section: Cytokines and Chemokine In The Serummentioning
confidence: 99%